Increased risk of hyperthyroidism induced by immune checkpoint inhibitors in patients with existing or prior Graves’ disease: a nested prospective cohort study with propensity score matching - Suzuki, Koji; Kobayashi, Tomoko; Izuchi, Tetsushi; Murase, Takanori; Ando, Masahiko; Handa, Tomoko; Onoue, Takeshi; Miyata, Takashi; Sugiyama, Mariko; Hagiwara, Daisuke; Suga, Hidetaka; Banno, Ryoichi; et al. (Frontiers in Endocrinology, 2025)
BackgroundThyroid dysfunction induced by immune checkpoint inhibitors (ICIs) commonly manifests as destructive thyroiditis and hypothyroidism, while hyperthyroidism (Graves’ disease) is rare. However, the clinical characteristics of thyroid dysfunction in patients with existing or prior Graves’ disease treated with ICIs remain unclear.MethodsA case-control study was performed using a prospective cohort of patients treated with ICIs between November 2015 and January 2024. At baseline, cases had Graves’ disease without overt thyroid dysfunction or prior Graves’ disease and were matched 1:5 with controls by age, gender, antithyroid antibody status at baseline, and ICI type. The incidence of thyroid dysfunction induced by ICIs was compared between cases and controls. The incidence of hyperthyroidism was compared with the exacerbation rate in ICI-untreated outpatients with Graves’ disease who were in remission or had no overt thyroid dysfunction for ≥1 year without changes in low-dose antithyroid medication.ResultsNineteen patients (13 in remission and 6 receiving thiamazole at baseline) were included and matched with 95 controls. During follow-up, 5 cases negative for thyroid-stimulating hormone receptor antibody (TRAb) at baseline developed thyrotoxicosis: 3 were TRAb-positive (2 with increased uptake on thyroid scintigraphy) suggesting hyperthyroidism, and 2 had destructive thyroiditis (TRAb-negative). The incidence of hyperthyroidism was significantly higher in cases than in controls (3/19 [15.8%] vs 0/95 [0%], p < 0.05), whereas the incidence of destructive thyroiditis (2/19 [10.5%] vs. 15/95 [15.8%], p = 0.734) or isolated hypothyroidism (0/19 [0%] vs. 13/95 [13.7%], p = 0.121) did not differ between groups. The incidence of hyperthyroidism was also higher in cases than in outpatients with ICI-unrelated Graves’ disease (3/19 [15.8%] vs 10/269 [3.7%], respectively; p < 0.05).ConclusionPatients with existing or prior Graves’ disease have an increased risk of hyperthyroidism following ICI treatment, highlighting their need for careful differential diagnosis of thyrotoxicosis.